Benefits and barriers associated with using cognitive–behavioral therapy to treat obsessive–compulsive disorder: a narrative review - Mukai, Keiichiro; Kyosuke, Yamanishi; Ogino, Shun; Hosoi, Yukihiko; Hayashida, Kazuhisa; Matsunaga, Hisato (Frontiers in Psychiatry, 2025)
There is a growing need for widely available, cost-effective, and low-intensity treatments for OCD. Although cognitive–behavioral therapy (CBT) is often the first line of treatment, barriers to providing CBT in OCD patients remain unresolved. In this narrative review, we summarize the current literature on the benefits and challenges of using CBT to treat OCD, review the potential of low-intensity, technology-based CBT programs, and identify issues related to the use of these new approaches. We identified articles to include in this narrative review by entering the following search terms into PubMed, PsychInfo, Web of Science, and Google Scholar: obsessive–compulsive disorder, OCD, cognitive–behavioral therapy, CBT, technolog*, digital. The final literature search was conducted on 13 July 2024, and after checking 68 potentially relevant studies according to our inclusion and exclusion criteria, we included 24 studies (14 review articles and 10 original articles) in the present review. We identified several main factors associated with the accessibility and effectiveness of CBT. Incentives for healthcare practitioners who undergo CBT training may increase the availability of this treatment option. Furthermore, treatment efficacy is related to patient treatment adherence, which may be enhanced by offering low-intensity and convenient treatment options such as digital CBT programs. These findings highlight both the potential and the current limitations of low-intensity and digital CBT approaches for OCD treatment. Although low-intensity and technology-based CBT programs can serve as relatively convenient, effective, and accessible treatment options, further research is needed to examine patient perceptions, and determine the most important characteristics of such programs for optimal treatment efficacy.